2020
DOI: 10.1136/bmjdrc-2019-000867
|View full text |Cite
|
Sign up to set email alerts
|

Improved diabetes control among low-income Mexican Americans through community-clinical interventions: results of an RCT

Abstract: IntroductionThis randomized controlled trial investigated community-clinical intervention strategies for a Mexican American population who had not demonstrated control of their diabetes. We tested a control program (Salud y Vida 1.0) supporting diabetes management versus an enhanced version (Salud y Vida 2.0) for reductions in HbA1c at 12 months.Research design and methodsAdults with uncontrolled diabetes (n=353) were enrolled if they had an HbA1c≥9.0% during a program or doctor’s visit between 6 and 36 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Rather, we aimed to investigate how different SDOH might contribute to the HbA1C reduction, after taking into account the participants' engagement in the program. We found that participants who attended more DSME classes had higher HbA1C reduction, which was consistent with the findings from Reininger et al ( 13 ), where high engagement groups (≥2 visits to service provided by intervention program) showed greater HbA1C reduction over the study period, but low engagement groups (<2 visits) were not able to maintain the reduction in HbA1C. We also included the length of day as a way to account for engagement, and found that a longer stay in the program was also associated with a higher reduction in HbA1C; however, the association had a plateau effect and diminished after 439 days.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Rather, we aimed to investigate how different SDOH might contribute to the HbA1C reduction, after taking into account the participants' engagement in the program. We found that participants who attended more DSME classes had higher HbA1C reduction, which was consistent with the findings from Reininger et al ( 13 ), where high engagement groups (≥2 visits to service provided by intervention program) showed greater HbA1C reduction over the study period, but low engagement groups (<2 visits) were not able to maintain the reduction in HbA1C. We also included the length of day as a way to account for engagement, and found that a longer stay in the program was also associated with a higher reduction in HbA1C; however, the association had a plateau effect and diminished after 439 days.…”
Section: Discussionsupporting
confidence: 93%
“…We should note that our analysis is not trying to provide a comprehensive evaluation of the effectiveness of the SyV program, as it has been reported elsewhere ( 13 ). Rather, we aimed to investigate how different SDOH might contribute to the HbA1C reduction, after taking into account the participants' engagement in the program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Examples include the use of drawings made by patients to assess their illness perception, 28 extended engagement with patients beyond the clinical setting using interventions that include peer led support groups, psycho-behavioural support, community based lifestyle programmes for patients and their families, and cooking classes. 29 …”
Section: Discussionmentioning
confidence: 99%
“…27 Examples include the use of drawings made by patients to assess their illness perception, 28 extended engagement with patients beyond the clinical setting using interventions that include peer led support groups, psycho-behavioural support, community based lifestyle programmes for patients and their families, and cooking classes. 29 We recommend a re-orientation of CDMPs to meet actual patient needs whereby the clubs focus on providing individualised self-management support to patients 11 consistent with their illness experience. Risk factors identified during yearly CDMP attendance should be adequately addressed through tailored self-management interventions and subsequent audits to assess effect of the interventions.…”
Section: Implications or Recommendationsmentioning
confidence: 99%